Vector calculus - Marsden, Jerrold E. (W. H. Freeman, 1976)
This acclaimed course in the calculus of functions of several variables and vector analysis is aimed mainly at second-year undergraduates. Marsden and Tromba provide a concrete, student-oriented text that fosters computational skills and intuitive understanding. The Fourth Edition maintains the balance between theory, applications, optional materials and historical notes present in earlier editions, but has been refined throughout. "This is a superbly produced book, whose clear and orderly presentation and informative diagrams immediately invite closer study ...The best way to evaluate a textbook is to teach from it, and it is clear from the companion study guide by Pao and Soon that it has passed this test.